Really want a whole? Or take it apart? Evidence of ESG disclosure heterogeneity on Chinese listed firm - Nam Kim (Global Business & Finance Review (GBFR), 2024)
Purpose: We examined how ESG disclosure and its sub-dimensions impact holding period returns, profitability, and company value. Design/methodology/approach: Utilizing Bloomberg panel data, the research investigates the effects of ESG dis-closures and their sub-dimensions on financial metrics within the Chinese stock market. Findings: Results reveal a multifaceted impact of ESG disclosures: environmental aspects positively affect returns, governance has a negative impact, and social factors show no significant effect. Overall ESG disclosures enhance Tobin's q, particularly driven by environmental factors. The study also identifies industry specific ESG effects and confirms ESG disclosure as a precursor to firm value, addressing endogeneity concerns. Research limitations/implications: The study offers vital insights for investors, guiding them on the differential impacts of ESG components on returns in China. It informs policymakers on crafting nuanced ESG disclosure regulations and encourages researchers to further explore ESG effects across industries and markets. Originality/value: This research uniquely dissects the disparate impacts of ESG dimensions on firm performance, emphasizing environmental disclosures and industry heterogeneity, especially during the COVID-19 pandemic. It advances the literature by detailing how various ESG facets affect firm performance, aiding stakeholders in aligning sustainability strategies with market expectations.
Keywords: 650; ESG disclosure; Emerging market; Environmental; Social; Governance; Chinese listed firm